2001
DOI: 10.1034/j.1600-0455.2001.042001043.x
|View full text |Cite
|
Sign up to set email alerts
|

CTA IN PATIENTS WITH ACUTE SUBARACHNOID HAEMORRHAGE. A comparative study with selective, digital angiography and blinded, independent review

Abstract: CTA in SAH is of great value in demonstrating vascular anatomy and the exact size of an aneurysm. However, IA-DSA is still needed for diagnostic evaluation in aneurysms smaller than 5 mm in diameter, especially in those located near bony structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 12 publications
(20 reference statements)
2
5
0
Order By: Relevance
“…In this study, males were more frequently exposed to SAH than females. This is not in concordance with most international studies, which have usually shown female preponderance (12,14,17,21,23). However, in another Finnish study by TAPANINAHO et al (20), the proportion of males was larger than females in their series of ruptured aneurysms.…”
Section: Discussionsupporting
confidence: 44%
“…In this study, males were more frequently exposed to SAH than females. This is not in concordance with most international studies, which have usually shown female preponderance (12,14,17,21,23). However, in another Finnish study by TAPANINAHO et al (20), the proportion of males was larger than females in their series of ruptured aneurysms.…”
Section: Discussionsupporting
confidence: 44%
“…We argue that the sensitivity of CTA may have been underestimated in some studies owing to misinterpretation of imaging scans potentially because of the lack of observer experience. Earlier investigations have shown that the accuracy of CTA detection of intracranial aneurysms can improve as the readers gain more experience or exposure 21 22 One study reported sensitivities for CTA increasing from 69% on initial aneurysms ( n =13) to 84% on subsequent aneurysms ( n =13) 22 .…”
Section: Discussionmentioning
confidence: 99%
“…In the event of negative CT angiography and a considerable suspicion of aneurysm, the patient should be examined further with conventional angiography. CT angiography may not identify aneurysms situated close to bony structures and aneurysms that measure less than 5 mm (42).…”
Section: Investigationmentioning
confidence: 99%